Conductance based characterization of structure and hopping site density in 2D molecule-nanoparticle arrays. Issue 36 (25th August 2015) - McCold, Cliff E.; Fu, Qiang; Howe, Jane Y.; Hihath, Joshua
Abstract : In nanoparticle-molecule monolayers, the distinction between macrostructural effects and nanoscale effects on the conductance distribution allows non-destructive determination of charge hopping site density. Abstract : Composite molecule-nanoparticle hybrid systems have recently emerged as important materials for applications ranging from chemical sensing to nanoscale electronics. However, creating reproducible and repeatable composite materials with precise properties has remained one of the primary challenges to the implementation of these technologies. Understanding the sources of variation that dominate the assembly and transport behavior is essential for the advancement of nanoparticle-array based devices. In this work, we use a combination of charge-transport measurements, electron microscopy, and optical characterization techniques to determine the role of morphology and structure on the charge transport properties of 2-dimensional monolayer arrays of molecularly-interlinked Au nanoparticles. Using these techniques we are able to determine the role of both assembly-dependent and particle-dependent defects on the conductivities of the films. These results demonstrate that assembly processes dominate the dispersion of conductance values, while nanoparticle and ligand features dictate the mean value of the conductance. By performing a systematic study of the conductance of these arrays as a function of nanoparticle size we are able to extract the carrier mobility for specific molecular ligands. We show that nanoparticle polydispersity correlates with the void density in the array, and that because of this correlation it is possible to accurately determine the void density within the array directly from conductance measurements. These results demonstrate that conductance-based measurements can be used to accurately and non-destructively determine the morphological and structural properties of these hybrid arrays, and thus provide a characterization platform that helps move 2-dimensional nanoparticle arrays toward robust and reproducible electronic systems.